Age determination from epiphysial fusion around elbow joint and their correlation with gender: a radiological study - Kaul, Archana; Kumar Rai, Rajesh; AgarwaL, Priyanka; Agarwal, Priyanka; Saroj, Shweta (Journal of Indian Academy of Forensic Medicine, 2021)
The present study aims to determine the age from epiphysis fusion around elbow joint. In this study, the X-ray films of the subjects were divided into three groups on the basis of degree of fusion. Firstly, those which were showing Non fusion (NF), secondly those showing Partial fusion (PF) & thirdly those showing Complete Fusion (CF). Observations made were compared with previous radiological studies. The fusion of conjoint epiphysis to shaft of humerus, upper end of radius and medial epicondyle with its shaft in male and female completed in all instances (100%) at the age groups of 17-18 years & 16-17 years respectively.